The genetics of body condition and leg weakness in the blue fox (Alopex lagopus) - Kempe, Riitta; Koskinen, Nita; Mäntysaari, Esa; Strandén, Ismo (Acta Agriculturae Scandinavica, Section A - Animal Science, 2010)
v 2010 ok